Acute inferior wall myocardial infarction associated with complete atrioventricular block and left posterior hemiblock. - Schamroth, L (1975)
Three cases of acute inferior wall myocardial infarction associated with complete atrioventricular block and junctional escape rhythm showing left posterior hemiblock are presented. The triad appears to consitiute a distinct syndrome. It is postuated that the subsidiary pacemaker is situated either in the bundle of His or the proximal part of the anterior division of the left bundle-branch.